The Effect of Adjusted Beta, Current Ratio, Total Asset Turnover, Debt To Equity Ratio, Return on Equity, And Price to Earnings Ratio To Stock Returns Of Manufacturing Companies Listed In Index LQ-45 In The Period Of 2015 - 2019. (Journal of Business and Management, 2021)
The development of economy allowing the people to be increasingly aware of investing’s importance. According to the Republic of Indonesia’s Ministry of Industry, investors invest up to Rp 216 trillion in the manufacturing industry. However, financial reports must be provided to provide a fair description of the company’s financial position and results of performance to the investors. The independent variables stated in this study are adjusted beta, liquidity ratio (CR), activity ratio (TATO), solvency ratio (DER), profitability ratio (ROE), and market ratio (PER). The dependent variable in this study is stock returns. This research is done as an applied research. This study uses secondary data; adjusted beta data from PEFINDO, company financial reports (www.idx.co.id) and historical prices (www.yahoofinance.com). The sampling technique was nonprobability sampling, namely purposive sampling. The results showed that CR and ROE had a partial effect on stock returns. Meanwhile, adjusted beta, CR, TATO, DER, ROE, and PER have a simultaneous effect on stock returns. These results are obtained from the tests that have been carried out.Keywords: Adjusted beta, Current Ratio, Total Assets Turnover, Debt to Equity Ratio, Return on Equity, Price Earning Ratio.